The Evolution of Linguistic Rights Throughout History and the Major Millestones - Awal, Abdul (PT FORMOSA CENDEKIA GLOBAL, 2023)
The evolution of linguistic rights represents a rich and consequential trajectory in the socio-political history of human societies. Mirroring broader shifts in political power, cultural paradigms, and technological advancements, linguistic rights have increasingly been recognized as a cornerstone of human rights and social justice. This paper embarks on a historical journey to trace the major milestones in the recognition, protection, and promotion of linguistic rights. Starting from the implicit recognition in ancient and medieval societies, it highlights the complex interplay of power, culture, and language. Concurrently, this period also sowed the seeds for a growing consciousness about the value of linguistic diversity. The paper critically examines the significant strides made in the 20th century, where international treaties and declarations explicitly acknowledged and championed linguistic rights. Here, the conversation around linguistic rights expanded to encompass dimensions of education, public administration, and more. In the 21st century, the digital age, the discourse on linguistic rights enters a new paradigm, shaped by the rise of technology and the internet. This period is marked by an increased awareness of digital linguistic divide and the potential of technology to both challenge and champion linguistic rights. Through a detailed exploration of these periods, the paper presents a holistic understanding of the development of linguistic rights. It underscores the enduring relationship between linguistic diversity, social justice, and national identity, and offers insights into the evolving global narrative on linguistic rights.